Phishfort – Anti-Phishing Framework - Abraham Kalloor, Eric; Manoj Kumar Mishra, Dr; Joy Paulose, Prof. (International Journal of Engineering and Technology, 2018)
Phishing attack is one of the most common form of attack used to get unauthorized access to usersâ€™ credentials or any other sensitive information. It is classified under social engineering attack, which means it is not a technical vulnerability. The attacker exploits the human nature to make mistake by fooling the user to think that a given web page is genuine and submitting confidential data into an embedded form, which is harvested by the attacker. A phishing page is often an exact replica of the legitimate page, the only noticeable difference is the URL. Normal users do not pay close attention to the URL every time, hence they are exploited by the attacker. This paper suggests a login framework which can be used independently or along with a browser extension which will act as a line of defense against such phishing attacks. The semi-automated login mechanism suggested in this paper eliminates the need for the user to be alert at all time, and it also provides a personalized login screen so that the user can to distinguish between a genuine and fake login page quite easily. Â Â